Job Market Perceptions of African Migrant Women in South Africa as an Initial and Long-Term Coping and Adaptation Mechanism - Ncube, A.; Bahta, Yonas T.; Jordaan, A. J. (Journal of international migration and integration, 2020)
This article assessed job market perceptions of African migrant women in South Africa as an initial and long-term coping and adaptation mechanism using a survey data, Kendall’s coefficient of concordance and Pearson’s chi-square. A questionnaire was used to collect data on demographic, socio-economic characteristics and socio-economic coping and adaptation mechanisms. Family, entrepreneurial, employment and humanitarian support was identified as coping mechanisms using the Sustainable Livelihood Framework. The results found that migrant women perceived the job market as conducive to employment. Strict labour polices in South Africa, however, forced migrant women to create jobs and to take any available job by deskilling their qualifications. The demographics, socio-economic characteristics and initial and long-term survival mechanisms played significant roles in the coping and adaptation mechanisms. The study recommends that the government clarify policies on business ownership of migrants in order to avoid conflicts. This could be done by providing more opportunities through good and relevant education systems and proactively learning from other countries who have managed to create valuable human capital bases.